Helicobacter pylori and unignorable extragastric diseases: Mechanism and implications - He, Junjian; Liu, Yunyi; Ouyang, Qin; Li, Rongxing; Li, Jie; Chen, Weiyan; Hu, Weichao; He, Lijiao; Bao, Qiyu; Li, Ping; Hu, Changjiang (Frontiers in Microbiology, 2022)
Considered as the most popular pathogen worldwide, Helicobacter pylori (H. pylori) is intensively associated with diverse gastric diseases, including gastric ulcers, chronic progressive gastritis, and gastric cancer. Aside from its pathogenic effect on gastric diseases, growing evidences reveal that H. pylori may be related to numerous extragastric diseases. In this article, we reviewed recent studies and systematically elucidated that H. pylori may interfere with many biological processes outside the stomach and influence the occurrence of various extragastric diseases. Many epidemiological studies have indicated that H. pylori plays a pathogenic role in COVID-19, atherosclerosis, hyperemesis gravidarum and several other extragastric diseases, while the effect of H. pylori is currently under investigation in gastroesophageal reflux disease, asthma, and inflammatory bowel disease. Moreover, we also summarized the possible pathogenic mechanisms of H. pylori that may be related to chronic systemic inflammation and molecular mimicker. Taken together, this review provides a new perspective on the role of H. pylori in extragastric diseases and explores the possible mechanisms, which may help guide clinical treatment.